1970
DOI: 10.1172/jci106323
|View full text |Cite
|
Sign up to set email alerts
|

Changes in serum and urinary calcium during phosphate depletion: studies on mechanisms

Abstract: ABSTRA CT The changes in serum calcium and the renal handling of this ion were evaluated during phosphate depletion. 96 renal clearance studies were carried out in 10 dogs before and after prolonged phosphate depletion (30-160 days) and after repletion. Depletion was produced by reducing phosphate intake and administering aluminum hydroxide gel while intakes of sodium, calcium, and magnesium were constant. With phosphate depletion, serum phosphorus fell to less than 1.0 mg/100 ml and diffusible serum calcium e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
1

Year Published

1973
1973
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(54 citation statements)
references
References 34 publications
5
48
1
Order By: Relevance
“…It is evident from clearance experiments that the urinary excretion of divalent cations of phosphate-depleted subjects is inappropriate for the plasma concentration, supporting the notion of defective tubular transport (153). Using micropuncture, we have demonstrated that defective magnesium absorption occurred in the loop of Henle and the distal tubule of phosphate-depleted dogs (156).…”
Section: Phosphate Depletionsupporting
confidence: 65%
See 2 more Smart Citations
“…It is evident from clearance experiments that the urinary excretion of divalent cations of phosphate-depleted subjects is inappropriate for the plasma concentration, supporting the notion of defective tubular transport (153). Using micropuncture, we have demonstrated that defective magnesium absorption occurred in the loop of Henle and the distal tubule of phosphate-depleted dogs (156).…”
Section: Phosphate Depletionsupporting
confidence: 65%
“…One of the hallmarks of hypophosphatemia and cellular phosphate-depletion is the striking increase in urinary excretion of calcium and magnesium (153). Magnesium excretion may be sufficiently large to lead to hypomagnesemia (154,155).…”
Section: Phosphate Depletionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is indirect evidence to indicate that the activity of the parathyroid glands is inhibited during phosphate depletion. Thus, rats show hypoplasia of the parathyroid glands during phosphate depletion (26); also serum calcium levels remain normal or slightly elevated after removal of the parathyroid glands in phosphate depleted rats (26,27) and dogs (20,28), indicating that serum so 7.10.…”
Section: Resultsmentioning
confidence: 99%
“…The aluminum or magnesium component of these drugs binds dietary phosphate, preventing its intestinal absorption and causing a negative phosphate balance typically within 3 to 4 weeks. The resulting hypophosphatemia is thought to prevent proper nucleation of mineral salts into the bone matrix, causing osteomalacia [6,11]. In addition, hypercalciuria can appear within 2 weeks [25] and, if not adequately supplemented in the diet, can lead to increased bone resorption via parathyroid hormone [2].…”
Section: Discussion and Treatmentmentioning
confidence: 99%